Pemerintahan Daerah dan Fasilitas Pendidikan Politik: Peluang dan Tantangan Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat - Teguh Ahmad Asparill (CV. Era Digital Nusantara, 2022)
Abstract: This research focuses on what is the role of the Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat of South Sulawesi Province in the implementation of political education based on the existing problems related to these activities. In this study, it was found that the role of the Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat in the implementation of political education in South Sulawesi Province had not been carried out properly, and there were several obstacles in the implementation process. Therefore, based on the research results, political education has not been implemented optimally due to several inhibiting factors. However, Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat of South Sulawesi Province have tried to overcome these obstacles so that later these activities can be carried out properly. Purpose: The purpose of this study was to analyze the role of the Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat of South Sulawesi Province in organizing political education facilitation whether it has been running optimally or at a minimum. Design/Methodology/Approach: The research method used in this research is descriptive qualitative with an inductive approach. The data collection techniques by means of interviews, observation, and documentation. Findings: In this study, it was found that the role of the Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat in organizing political education in South Sulawesi Province had not been carried out properly, and there were several obstacles in the implementation process. Originality/Value: The context of this research is then more focused on the implementation of the duties, principles, and functions of the Badan Kesatuan Bangsa, Politik dan Perlindungan Masyarakat of South Sulawesi Province in the administration of political education facilities when viewed from the aspects of norms, organization, and social structure.